Effect of counter body on wear behavior of plasma-sprayed TiO2-45Cr2O3 coating. - Kücük, Yılmaz (Taylor & Francis Ltd, 2021)
The aim of this study was to determine the counter body effect on the wear behavior of TiO2-45 Cr2O3 coating. The commercial TiO2-45 Cr2O3 coating powder was deposited onto the surface of the AISI 316 L substrate using the APS method. Dry sliding wear tests were performed with Al2O3 and WC-Co counter body balls under different loads (5 N, 10 N, and 15 N) and reciprocating frequencies (1 Hz, 2 Hz, and 3 Hz). The COF values obtained from the Al2O3 ball were found to be higher than that of the WC-Co ball. In general, increasing load and sliding speed caused higher wear volume values for both counter body balls. When using Al2O3 ball under the 5 N load, a higher amount of wear debris and crack formation was observed, whereas, for higher loads, a larger plastic deformation zone which has lots of pitting and spalling was determined. As for the WC-Co ball, swelling-induced spallation and delamination were recorded as the effective wear mechanisms as well as the plastic deformation.
Keywords: Aps; Tio(2)-45 Cr2o3 Coating; Dry Sliding Wear; Reciprocating Test